Community Coalition Efforts to Prevent Adolescent Substance Use: A Systematic Review. (March 2021) - Hutchison, Morica; Russell, Beth S.
A systematic review explored the creation and maintenance of community coalitions as effective for alcohol and other drug (AOD) prevention in adolescence. Community coalitions influence the implementation of effective and sustainable community-based prevention via infrastructure supporting development, delivery, and assessment of human service issues. For this review, 1, 435 articles were identified, most including insufficient detail on the purposes and activities of coalitions or focus on adolescents. Of the 16 studies included, few discussed comprehensive frameworks describing coalition formation and maintenance or measureable influences on adolescent AOD prevention outcomes. Therefore, we propose four organizing principles for building sustainable community coalitions for adolescent AOD prevention.